Ameliorative effects of omega-lycotoxin-Gsp2671e purified from the spider venom of Lycosa praegrandis on memory deficits of glutamate-induced excitotoxicity rat model - Keimasi, Mohammad; Salehifard, Kowsar; Shahidi, Marzieh; Esmaeili, Fariba; Mirshah Jafar Esfahani, Noushin; Beheshti, Siamak; Amirsadri, Mohammadreza; Naseri, Faezeh; Keimasi, Mohammadjavad; Ghorbani, Najmeh; Mofid, Mohammad Reza; Moradmand, Majid (Frontiers in Pharmacology, 2022)
Memory impairment is one of the main complications of Alzheimer's disease (AD). This condition can be induced by hyper-stimulation of N-Methyl-D-aspartate receptors (NMDARs) of glutamate in the hippocampus, which ends up to pyramidal neurons determination. The release of neurotransmitters relies on voltage-gated calcium channels (VGCCs) such as P/Q-types. Omega-lycotoxin-Gsp2671e (OLG1e) is a P/Q-type VGCC modulator with high affinity and selectivity. This bio-active small protein was purified and identified from the Lycosa praegrandis venom. The effect of this state-dependent low molecular weight P/Q-type calcium modulator on rats was investigated via glutamate-induced excitotoxicity by N-Methyl-D-aspartate. Also, Electrophysiological amplitude of field excitatory postsynaptic potentials (fEPSPs) in the input–output and LTP curves were recorded in mossy fiber and the amount of synaptophysin (SYN), synaptosomal-associated protein, 25kDa (SNAP-25), and synaptotagmin 1(SYT1) genes expression were measured using Real-time PCR technique for synaptic quantification. The outcomes of the current study suggest that OLG1e as a P/Q-type VGCC modulator has an ameliorative effect on excitotoxicity‑induced memory defects and prevents the impairment of pyramidal neurons in the rat hippocampus.